PENGARUH PERMAINAN KERETA ANGKA TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DI PAUD LESTARI KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR - Sari, Nurmala; Novianti, Ria; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the result of observation in the field toward the concept of numbers ability of children are not yet improve optimally. So,it is needed apply train numbers game. This research of apply train numbers game toward the concept of numbers ability in 4-5 years old children at Lestari kindergarden districts Kemuning district Indragiri Hilir. Sample of this research are 20 student of class. Technique to college data is using observation. technique of data analysis is using t-test with using SPSS 16.0 program. Hypotheses of this research is there are very significant the effect of train numbers game toward the concept of numbers of ability in 4-5 years old children at lestari kindergarten kemuning districts indragiri hilir district. This is knowing from the result of data obtained t=20,7751 p=0,000 because p < 0,05. So, it can be conclude that there has a very significant different of children concept of numbers after using train numbers game in teaching learning. So, its mean that Ho refused and Ha accepted that means there are very significant different between before and after doing the experiment with train numbers game. the effect of train numbers game toward the concept of numbers ability in 4-5 years old children at lestari kindergarten districts kemuning district indragiri hilir as much as 50,7%.Key Words : Numbers Concept, Train Number Game